Environmental Applications of Remote Sensing 2016
DOI: 10.5772/61853
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Multichannel Remote-Sensing Images with Prediction of Performance Parameters

Abstract: In processing of multichannel remote sensing data, there is a need in automation of basic operations as filtering and compression. Automation presumes undertaking a decision on expedience of image filtering. Automation also deals with obtaining of information based on which certain decisions can be undertaken or parameters of processing algorithms can be chosen. For the considered operations of denoising and lossy compression, it is shown that their basic performance characteristics can be quite easily predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 49 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…It is di±cult to thoroughly study all these subtasks within the scope of a paper. Earlier studies 33,38,51 have shown the following. Firstly, there exist quite simple statistics of DCT coe±cients which can serve as good input parameters.…”
Section: Filtering E±ciency Predictionmentioning
confidence: 85%
See 3 more Smart Citations
“…It is di±cult to thoroughly study all these subtasks within the scope of a paper. Earlier studies 33,38,51 have shown the following. Firstly, there exist quite simple statistics of DCT coe±cients which can serve as good input parameters.…”
Section: Filtering E±ciency Predictionmentioning
confidence: 85%
“…Secondly, it has been already demonstrated that IPSNR for many¯lters can be predicted quite accurately for DCT-based¯lters 1,33,38,51 and some other denoising techniques. 34 Accuracy can be characterized di®erently where the root mean square error (RMSE) of estimates is one of the most adequate and widely used quantitative criteria.…”
Section: Filtering E±ciency Predictionmentioning
confidence: 99%
See 2 more Smart Citations